Tunable sensitivity microfiber Sagnac loop based on a virtual reference arm for microdisplacement detection - Yang, Peng; Jiang, Shaocui; Wang, Zenghui; Bao, Wangge; Wei, Wenxi; Zhang, Yujuan; Zheng, Jia; Peng, Baojin (Optical fiber technology, 2023)
•High sensitivity interferometric microdisplacement optical fiber sensor.•High extinction ratio microfiber Sagnac loop.•Online Vernier with tunable sensitivity.•Virtual reference arms are used to reduce costs and volume.•The virtual reference arm has high stability and is not subject to external interference. A virtual reference arm-based microfiber Sagnac ring (MFSL) microdisplacement sensor with tunable sensitivity is proposed and demonstrated in this study. We abandon the traditional physical reference arm and build a virtual reference arm to overcome the disadvantage of the physical reference arm being susceptible to environmental influences and to achieve tunable sensitivity. A MFSL with a diameter of 4 μm was fabricated via the winding and tapering process, and a microdisplacement sensitivity of −0.34 nm/μm was obtained in the range of 0–5 μm. Experimental results show that the microdisplacement sensitivity can reach −1.40 nm/μm after cascading the simulated reference arm, which is 4.12 times that of single MFSL. In addition, by changing the parameters of the virtual reference arm without remaking the reference arm, we obtained sensors with sensitivities of −1.74 and −2.30 nm/μm. The sensor has advantages of tunable sensitivity and low cost and has potential applications in microdisplacement measurement.